2018
DOI: 10.3201/eid2405.171859
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic Hemorrhagic Disease Virus Serotype 6 Infection in Cattle, Japan, 2015

Abstract: During October–December 2015, an epizootic hemorrhagic disease outbreak occurred in cattle in Japan. Forty-six animals displayed fever, anorexia, cessation of rumination, salivation, and dysphagia. Virologic, serologic, and pathologic investigations revealed the causative agent was epizootic hemorrhagic disease virus serotype 6. Further virus characterization is needed to determine virus pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…A large number of EHDV mortality was reported in United States during summer and fall of 2012, including multiple species cattle (129 herds), captive white-tailed deer (65 herds), bison (8 herds), yak (6 herds) elk (1 herd) and sheep (1 flock). The average mortality withinherd morbidity was 7% in cattle and bison herds, and 46% in captive white-tailed deer herds and the average within-herd mortality in captive white-tailed deer herds was 42% [40]. However, the major observation can be found as high temperatures facilitate the transmission of EHD virus by C. sonorensis midges by decreasing the extrinsic incubation period of the virus.…”
Section: Discussionmentioning
confidence: 97%
“…A large number of EHDV mortality was reported in United States during summer and fall of 2012, including multiple species cattle (129 herds), captive white-tailed deer (65 herds), bison (8 herds), yak (6 herds) elk (1 herd) and sheep (1 flock). The average mortality withinherd morbidity was 7% in cattle and bison herds, and 46% in captive white-tailed deer herds and the average within-herd mortality in captive white-tailed deer herds was 42% [40]. However, the major observation can be found as high temperatures facilitate the transmission of EHD virus by C. sonorensis midges by decreasing the extrinsic incubation period of the virus.…”
Section: Discussionmentioning
confidence: 97%
“…This is much fewer compared to the over 400 complete genomes available for BTV (http://btv.glue.cvr.ac.uk/#/home). Despite the recent EHDV-6 outbreaks in beef and dairy cattle in Israel (Golender et al, 2017) and Japan (Kamomae et al, 2018) during 2015, and the many EHDV-6 outbreaks observed in Mediterranean countries, there are currently only six complete genomes of EHDV-6 available in GenBank. Three of these sequences are from EHDV-6 isolates from the 1980s and 1990s (AUS1981/07, BAR1983/01, and M44/96), and the remaining three are from the USA (CC 304-06, 12-3437-8, OV208).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our data clearly indicate that EHDV-7 infection caused fever in eight cattle bred at a farm in Fukuoka. In recent decades, epizootics of EHD in cattle have been reported in many countries in Asia and the Mediterranean basin [6,9,10,11,13,16,23,29,35,40].…”
Section: Analytical Specificity and Sensitivity Of The Modified Rt-pcr Assaymentioning
confidence: 99%